An analysis of the elementary school music teaching course in Turkey - Özgül, Ilhan (SAGE Publications, 2009)
In this article, I discuss the Turkish elementary school music teaching course in terms of the requirements of the Turkish elementary music curriculum and those of other countries such as the USA, Ireland and Malta. I propose that a more effective and efficient method of elementary music teacher preparation be put in place based on findings from research conducted in Turkey, and what is currently considered sound practice within the field of education in general and the music education profession.
Keywords: 4. Education